The Role of Identification in Ending Child Marriage - Hanmer, Lucia; Elefante, Marina (World Bank, Washington, DC, 2016)
The 2030 Agenda for Sustainable Development’s Goal for Gender Equality (SDG5 to: Achieve Gender Equality and Empower Women and Girls) sets a series of ambitious targets that will measure progress towards attaining this goal. One such target is to: ‘eliminate all harmful practices, such as child, early and forced marriage and female genital mutilation. In this paper we examine how efforts to achieve legal identity for all, including birth registration for all, can contribute to ending child marriage. The authors begin by setting out the current context presenting data on child marriage and its impacts and then turn to birth registration drawing out its links with fundamental human rights and development goals. We then present estimates of the numbers of unregistered children in the world’s global regions based on the World Bank Identification for Development Initiative (ID4D) dataset. The authors turn next to the link between birth registration and child marriage rates6 using data on birth registration in the 106 countries for which authors also have data on child marriage. The authors find a correlation between high birth registration rates and low child marriage rates and discuss this link in the context of evidence on the underlying causes and drivers of child marriage. The authors explore the links between birth registration and child marriage in greater depth in two case studies: the first one examines the role of identity papers, particularly birth and marriage certificates, in the enforcement of minimum age of marriage laws for Syrian refugees in Jordan; the second one discusses how a recently adopted strategy to streamline the process for obtaining birth certificates in Indonesia can contribute to reducing child marriage. Despite evidence of a correlation, however, a policy pursuing universal birth registration is unlikely to have impact on child marriage rates unless it is embedded in broader efforts to end child marriage, including legal reform, advocacy, and national and local policies and programs which work with communities to change social norms and are designed to reach people that are at risk from being excluded from national efforts, for example refugees and internally displaced peoples.